STAN UMYSŁU - Lipko, Daria (Poland, 2016)
Bosnian Muslim Prof. Senadin Ljubovic and Bosnian Serb, Dr. Radovan Karadzic are old friends who used to work together in a psychiatric clinic in Sarajevo. The war put them on two different sides of the conflict. Twenty years later, Prof. Ljubovic decides to travel to Scheveningen where Karadzic is awaiting a sentence of the International Court of Justice. “State of Mind” is a documentary film that serves as a unique journey into the depths of human nature, in general, and of post-conflict traumas, in specific.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films